Variations of sex-hormones in reproductive aged females do not impact the repeated bout effect following maximal unaccustomed eccentric exercise of the elbow flexors - Rilling, Amelia; Power, Geoffrey A. (Biology of Sport, 2025)
Neuromuscular function is impaired following unaccustomed eccentric exercise, the repeated bout effect (RBE) however, protects from damage following a subsequent bout. Muscle damage may be mitigated in females due to protective effects of estradiol. The purpose of this study was to investigate the relationship between the follicular phase of the menstrual cycle and oral contraceptive use on neuromuscular impairments following damaging eccentric exercise and the magnitude of the RBE. Fifteen female participants (18–30 years) performed two bouts of 150 maximal eccentric contractions of the elbow flexors four weeks apart. Normally menstruating females were tested during the late follicular phase (day:10–14) of their menstrual cycle, when estradiol is near peak. Oral contraceptive users were tested on their placebo pill days (lower estradiol). Neuromuscular function following Bout1 and Bout2 (4 weeks later), was assessed using both voluntary (maximal voluntary contraction torque; MVC, voluntary activation; VA), and electrically evoked contractions (peak twitch torque, 10 Hz and 100 Hz torque). For both groups, following Bout1, there was a 16% decrease in MVC torque ( p < 0.05), and soreness increased ~20-fold ( p < 0.05). Following Bout 2, both groups recovered to baseline values by 48 hrs for MVC torque, and the magnitude of the RBE was similar between groups ( p > 0.05). Females in the late follicular phase (classified as high estradiol) and females on combined oral contraceptives (low estradiol) had similar impairments in neuromuscular function following the first bout of eccentric exercise, and a similar RBE.